Bacterial community composition and function in different habitats in Antarctic Fildes region revealed by high-throughput sequencing - Zhang, Yi-He; Hu, Yong-Qiang; Zeng, Yin-Xin; Hu, Ting; Han, Wei; Du, Yu; Hu, Zhong; Meng, Shan-Shan (Frontiers in Microbiology, 2025)
IntroductionPristine soil, ornithogenic soil, intertidal sediment, and marine sediment represent four of typical habitats in the Fildes region, maritime Antarctica. However, information on bacterial community composition and function in these Antarctic habitats remain limited.MethodsIn this study, using a combination of 16S rRNA gene amplicon sequencing and shotgun metagenomic sequencing, 12 samples collected from various habitats in the region were analyzed.Results and discussionBacterial community compositions in terrestrial habitats (i.e., pristine and ornithogenic soils) were found to be distinct (p < 0.01) from those in marine habitats (i.e., marine and intertidal sediments). Organic carbon (p < 0.01) and pH (p < 0.01) were two major environmental factors affecting the bacterial community composition in the diverse habitats. Proteobacteria (represented by Gamma-, Alpha-, and Betaproteobacteria; > 30%), Actinobacteria (represented by Actinobacteria; > 20%), and Bacteroidetes (represented by Flavobacteriia; > 10%) were dominant in bacteria related to carbon, nitrogen, and sulfur metabolism across all samples. Though most metabolic pathways were common in both terrestrial and marine habitats, terrestrial samples showed more diverse metabolic pathways than marine samples. However, among the top 15 abundant metabolic pathways, genes related to 11 metabolic pathways were relatively more abundant in marine habitats than in terrestrial habitats (p < 0.05). More abundant genes related to methane metabolism (e.g., pmoA), nitrification (e.g., amoA and hao), reductive citrate cycle pathway (e.g., frdA), repair of DNA damage (e.g., lexA and uvrB), salt and osmotic stress tolerance (e.g., betB, gltB, and treS), and aromatic hydrocarbon degradation (e.g., bcrC and bssA) were detected in pristine and/or ornithogenic soils, whereas genes related to sulfur metabolism (e.g., soxY, fccB, dsrAB, and sat), nitrogen fixation (e.g., nifH), acetyl-CoA metabolism (e.g., acsB, cdhD, and cdhE), carbohydrate degradation (e.g., amyA and chiA), and cold adaptation (e.g., cspA, deaD and recQ) were in higher abundance in marine and/or intertidal sediments. The influence of penguin feces on soil bacterial community composition and ecological function was observed in this study. The study findings will improve our understanding of bacterial community composition and function in various habitats in maritime Antarctica under the background of global climate change.